Telaah Argumentasi Kajian Integrasi Ilmu dan Agama - Ni'mah, Zetty Azizatun (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
Muslims who perceive that Islamic teachings only include fiqh, monotheism, tasawaf morals, interpretations, etc., whether they realize it or not, make Muslims left behind by other communities. The progress of human civilization is not produced by the advancement of religious knowledge but by technology and science. The thought struggle between religion and science then raises questions about solving concepts, namely the integration of science and religion which must be immediately applied in the world of education. Efforts to integrate the dichotomy of knowledge in Islamic education can be carried out using the approach of integrating knowledge in Islamic education. One of them is changing the orientation of Islamic education from a tendency only towards ritual worship towards carrying out ritual and social worship together, changing the orientation of Islamic education from just educating to understand religious sciences to understanding religious sciences as well as social sciences, humanities. and natural sciences. These sciences must be understood convergently by taking an interdisciplinary approach so that students understand and can understand the solutions to the complexity of the problems faced by society.   Keywords: Integration, Knowledge, Religion…